Collagen-Covered Autologous Chondrocyte Implantation Versus Autologous Matrix-Induced Chondrogenesis: A Randomized Trial Comparing 2 Methods for Repair of Cartilage Defects of the Knee. Issue 9 (17th September 2019) - Fossum, Vegard; Hansen, Ann Kristin; Wilsgaard, Tom; Knutsen, Gunnar
Background: Autologous matrix-induced chondrogenesis (AMIC) is a single-stage alternative to autologous chondrocyte implantation for treatment of localized cartilage defects of the knee. To our knowledge, no randomized controlled trial exists comparing the 2 methods. Purpose: To evaluate any difference in the outcome of AMIC as compared with collagen-covered autologous chondrocyte implantation (ACI-C). Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A prospective randomized controlled clinical trial was designed to assess any differences in the outcomes between ACI-C and AMIC for the treatment of ≥1 chondral or osteochondral defects of the distal femur and/or patella. The inclusion period was set to 3 years, and the aim was to include 80 patients (40 in each group). Patient inclusion was broad, with few exclusion criteria. The primary outcome was change in Knee injury and Osteoarthritis Outcome Score (KOOS) at 2 years as compared with baseline. The secondary outcomes were the number of failures in each group at 2 years and the change in KOOS subscale, Lysholm, and pain visual analog scale (VAS) scores at 2 years as compared with baseline. A 2-sample t test with a significance level of P < .05 was used to compare the change in score from baseline between groups. Results: A total of 41 patients over 3 years were included in the study: 21 in the ACI-C group and 20 in the AMIC group. All the patients had prior surgery to the index knee. At 2-year follow-up, the clinical scores for both groups improved significantly from baseline. No significant differences between groups were seen in the change from baseline for KOOS (AMIC, 18.1; ACI-C, 10.3), any of the KOOS subscales, the Lysholm score (AMIC, 19.7; ACI-C, 17.0), or the VAS pain score (AMIC, 30.6; ACI-C, 19.6). Two patients in the AMIC group had progressed to a total knee replacement by the 2-year follow-up as compared with none in the ACI-C group. Conclusion: At 2-year follow-up, no significant differences were found regarding outcomes between ACI-C and AMIC. Mid- and long-term results will be important. Registration: NCT01458782 (ClinicalTrials.gov identifier).